2013
DOI: 10.1007/s10750-013-1665-8
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of invasive crayfish (Pacifastacus leniusculus) on endangered freshwater pearl mussels (Margaritifera laevis and M. togakushiensis) in Japan

Abstract: The invasive alien crayfish Pacifastacus leniusculus is considered harmful to freshwater pearl mussels Margaritifera laevis and M. togakushiensis. It also often colonises mussel habitats in Japan. In order to test the negative effects of alien crayfish on mussels, we evaluated the predation impact of signal crayfish on freshwater pearl mussels in vitro. We tested the relationship between the survival/injury rates of mussels and crayfish predation with respect to different sizes of mussels (four classes based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 15 publications
7
26
0
Order By: Relevance
“…This comes as no surprise since other crayfish species are known to prey freshwater bivalves (e.g. Klocker and Strayer, 2004;Perry et al, 1997) and Machida and Akiyama (2013) showed that P. leniusculus was capable of preying two endangered Margaritifera species.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This comes as no surprise since other crayfish species are known to prey freshwater bivalves (e.g. Klocker and Strayer, 2004;Perry et al, 1997) and Machida and Akiyama (2013) showed that P. leniusculus was capable of preying two endangered Margaritifera species.…”
Section: Discussionmentioning
confidence: 99%
“…of medium size and suggested that this size class was the most suitable for crayfish manipulation. Nonetheless, and based on Machida and Akiyama (2013) results, these crayfishes may also kill small immature mussels. Besides this, in our study, crayfish size did not affect predation, which shows that smaller crayfishes are as capable of preying bivalves of various sizes as their larger counterparts.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations